Distribution of Oxygen at the Ni81Fe19/Ta Interface - T. J. A. Mori; R. D. D. Pace; W. H. Flores; M. Carara; L. F. Schelp; L. S. Dorneles (Advances in Materials Science and Engineering)
The knowledge of how oxygen atoms are distributed at a magnetic-metal/oxide, or magnetic-metal/non-magnetic-metal interface, can be a useful tool to optimize device production. Multilayered Ni81Fe19/Ta samples consisting of 15 bilayers of 2.5 nm each, grown onto glass substrates by magnetron sputtering from Ni81Fe19 and Ta targets, have been investigated. X-ray absorption near edge structure, extended X-ray absorption fine structure, small angle X-ray diffraction, and simulations were used to characterize the samples. Oxygen atoms incorporated onto Ni81Fe19 films during O2 exposition are mainly bonded to Fe atoms. This partial oxidation of the Ni81Fe19 surface works as a barrier to arriving Ta atoms, preventing intermixing at the Ni81Fe19/Ta interface. The reduction of the Ni81Fe19 surface by the formation of TaOx is observed.